335 RISK FACTORS FOR SPONTANEOUS INTESTINAL PERFORATION IN EXTREMELY LOW BIRTH WEIGHT NEONATES. Issue 1 (1st January 2007) - Davis, K. F.; Ahmad, I.; Emil, S.
Abstract : Purpose of Study: Spontaneous intestinal perforations (SIP) in extremely low birth weight (ELBW) neonates are distinctly different from necrotizing enterocolitis (NEC) and appear to be increasing in incidence. The etiology of SIP is not well understood. We performed a retrospective cohort study to identify potential patient characteristics, as well as perinatal and neonatal therapeutic interventions that may increase the risk of SIP. Methods: All ELBW (< 1, 000 g) infants admitted to a neonatal intensive care unit during a recent 42-month period were studied. Infants with radiologic or histologic diagnosis of NEC were excluded. Infants with SIP were compared with infants with no perforation (NP). Chi-square and paired t -tests were used for statistical comparisons between the two groups. Mean values are given with standard error of the mean. Summary of Results: There were 13 cases of SIP identified and 165 NP controls. The mean gestational age was lower for the SIP group, but this did not reach statistical significance (SIP 25.85 ± 0.56 vs NP 26.18 ± 0.16 weeks, p = .46). Likewise, the mean birth weight was comparable for both groups (SIP 732.5 ± 40.07 g and NP 758.1 ± 11.53 g, p = .46). There was no statistical difference in the use of antenatal maternal steroids (SIP 61.5% vs NP 43.6%, p ≤ .25). There were no significant differences in maternal indomethacin (SIP 7.7% vs NP 9.7%) or magnesium sulfate use (38.5% vs 40%). In contrast, there was a significantly higher incidence of terbutaline use in mothers of SIP infants (30.77% vs 9.09%, p ≤ .025). Use of indomethacin in neonates was higher in the SIP group; however, the difference did not reach statistical significance (SIP 69.23% vs NP 56.36%, p ≤ .24). Hydrocortisone administration in the first 16 days of life was higher in the SIP group versus NP, but this also did not reach statistical significance (15.38% vs 10.9%, p ≤ .24). Conclusions Reached: Contrary to previous reports, indomethacin does not appear to increase the risk of SIP. Tertbutaline tocolysis of the mother is associated with increased risk for development of SIP in premature infants. Prospective studies need to be designed to confirm this association. In the meantime, a high index of suspicion for SIP must be maintained in preterm infants exposed to maternal terbutaline.